Implementasi IoT dalam Pengaturan Sistem untuk Peningkatan Kualitas Distribusi Air Pamsimas di Gunungpati - Rafi Wicaksono; Dita Riyani; Rofik Widdayanto; Eka Nuryanto Budisusila (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2025)
Clean water distribution in the Community-Based Drinking Water Supply and Sanitation Program (PAMSIMAS) in Kuwasen Lama Village, Gunungpati District, Semarang City, faces the challenge of unequal supply between highland and lowland areas. The main factors that affect these conditions include differences in topography, suboptimal piping network design, and unbalanced water pressure, especially during peak hours. This research proposes a solution based on Internet of Things (IoT) technology using the ESP32 module as a control center, which is integrated with the Blynk application for real-time monitoring and control of the system. The system is equipped with a water flow sensor, water level sensor, motorized valve, and booster pump to increase water pressure in high elevation areas. Two design schemes were tested, namely flow regulation using a motorized valve, and a combination of a motorized valve with a booster pump. The results of the simulation and implementation showed an increase in water pressure stability, equitable distribution, and a decrease in the frequency of supply disruptions. The system also allows for live monitoring of network conditions, facilitates technical decision-making, and improves operational efficiency. With an adaptive and community participation-based approach, this solution has the potential to become a model for PAMSIMAS clean water distribution management that is efficient, sustainable, and responsive to geographical challenges, while strengthening the resilience of clean water services in rural areas.